Distinct Mechanisms Underlying Pronociceptive Effects of Opioids - Heinl, Céline; Drdla-Schutting, Ruth; Xanthos, Dimitris N.; Sandkühler, Jürgen (The Journal of neuroscience, 2011)
In addition to analgesia, opioids may also produce paradoxical pain amplification [opioid-induced hyperalgesia (OIH)] either on abrupt withdrawal or during continuous long-term application. Here, we assessed antinociceptive and pronociceptive effects of three clinically used opioids at C-fiber synapses in the rat spinal dorsal horn in vivo . During 60 min of intravenous infusions of remifentanil (450 μg·kg −1 ·h −1 ), fentanyl (48 μg·kg −1 ·h −1 ), or morphine (14 mg·kg −1 ·h −1 ), C-fiber-evoked field potentials were depressed and paired-pulse ratios (PPR) were increased, indicating a presynaptic inhibition by all three opioids. After withdrawal, postsynaptic responses were enhanced substantially for the remaining of the recording periods of at least 3 h. Withdrawal from remifentanil led to long-term potentiation (LTP) of synaptic strength in C-fibers via activation of spinal μ-opioid receptors (MORs) and spinal NMDA receptors (NMDARs). Fentanyl and morphine caused an enhancement of synaptic transmission at C-fibers, which involved two distinct mechanisms: (1) an opioid withdrawal LTP that also required activation of spinal MORs and NMDARs and that was associated with a decrease in PPR suggestive of a presynaptic mechanism of its expression, and (2) an immediate-onset, descending facilitation of C-fiber-evoked field potentials during and after intravenous infusion of fentanyl and morphine. Immediate-onset, descending facilitation was mediated by the activation of extraspinal MORs, descending serotonergic pathways, and spinal 5-hydroxytryptamine-3 receptors (5-HT 3 Rs). Our study identified fundamentally different pronociceptive effects of clinically used opioids and suggests that OIH can be prevented by the combined use of NMDAR and 5-HT 3 R antagonists.